The Road Less Travelled: My Story as an International Student (Comparative & International Education Series, 2022)
It is such a huge privilege to share my experience of studying and being supported as an international student studying in the United States. After months of planning, studying, writing, and passing the Test of English as a First Language (TOEFL) exam and going through the immigration processes, I got accepted into a US school. In January 2016, I left Nigeria for the US with three young children–ages seven, five, and 16 months. And after more than a 24-hour journey, and two layovers, I arrived in the US. I started my graduate studies at the Hugo Wall School of Public Affairs, Wichita State University, Wichita, Kansas.